EDITORIAL - Meltem Alkan Melikoglu, (Archives of Rheumatology, 2023)
Greetings from the new Editor, As the new Editorial Team, we are pleased to announce that we are ready to present the June 2023 issue of the Archives of Rheumatology. Our journal serves as the official publication organ of the Turkish League Against Rheumatism (TLAR), since it was first published in May 1955 under a different name. Our current issue comprises a number of essential highlights among many other papers. The first one is an “invited narrative review” entitled “The ABCs of Antiphospholipid Syndrome” which was prepared by Ayse Bahar Kelesoglu Dincer and Doruk Erkan.[1] I am deeply grateful to the authors for their kind acceptance to our invitation and their significant contribution to our current issue. The June issue also consists of a study on a popular topic that investigates risk factors for the progression and prognosis of connective tissue disease-associated interstitial lung disease.[2] Also, Ertilav et al.[3] compared radiological and clinical results of knee intra-articular injection with two ultrasonography-guided techniques in a randomized-controlled study. There are also essential articles on rheumatoid arthritis, spondyloarthritis, Behçet’s disease, systemic sclerosis, fibromyalgia, juvenile rheumatic diseases, and imaging studies in rheumatic diseases. I hope all articles will provide a significant contribution to the body of knowledge in the literature. The Editorial Team of the Archives of Rheumatology has changed in June 2023. Ilker YAGCI, our previous Editor-in-Chief, handled the manuscripts of the March issue. I would like to thank him for his vision and great efforts for the improvement of the journal. I would also like to thank previous editorial team members, namely Sibel Unsal DELIALIOGLU, F. Figen AYHAN, Esra GIRAY, Zafer GUNENDI, Ozgur KASAPCOPUR, Ozgur AKGUL, Ilke Coskun BENLIDAYI, Ozge KENIS, Olena ZIMBA, and Armen Yuri GASPARYAN for their valuable contributions to our journal. This marvelous team did a great job in advancing and allowing the journal to be established as an important source of rheumatology practice. Let me come to an end of these greetings by also thanking all our previous Editorial Teams, Board members, reviewers, authors, and readers for their valuable efforts during the past 68 years of the journal. Finally, as the new Editorial Team, we shall do our best to carry the journal even further on this path and hopefully enhance its impact in its field. Individually, it will be a lifelong honor to me to be the Editor-in-Chief of the Archives of Rheumatology.